Lipid rafts: microenvironments for integrin–growth factor interactions in neural development. (1st June 2004) - Decker, L.; Baron, W.; ffrench-Constant, C.
Abstract : The development of a complex multicellular organ such as the nervous system requires precise regulation of cell migration, proliferation and survival. This regulation in turn requires the integration of long-range signals, such as growth factors, with short-range cues that define the precise location and cellular neighbours for any given cell. This short review examines one integrative mechanism, integrin–growth factor receptor interactions, and explores the role of lipid rafts in the molecular mechanisms that underlie the receptor interactions.